2018
DOI: 10.1177/0890334418773304
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perception of Adequacy of Mother’s Milk Among Mothers Giving Birth at a Teaching Hospital in Sri Lanka

Abstract: Sri Lankan family members should be educated further about normal patterns of milk production during the postpartum period. The authors recommend that PIM be included in screening tools for postpartum depression in Sri Lanka.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The SRIM risk factors very consistently identified were low maternal education (five of six studies examining this risk factor) (Gokceoglu & Kucukoglu, 2017; Menekseet al, 2021; Robert et al, 2014; Rodrigo et al, 2019; Segura‐Millán et al, 1994), primiparity (five of nine studies) (Brownell et al, 2012; Hillervik‐Lindquist, 1992; Keemer, 2013; Kent et al, 2021; Kirkland & Fein, 2003), maternal employment (three of three studies) (Chuang et al, 2007; Sahin et al, 2013; Sun‐Hee, 2019), and younger maternal age (five of six studies) (Amine et al, 1989; Brown et al, 2014; Gokceoglu & Kucukoglu, 2017; López et al, 2013; Rodrigo et al, 2019). On the other hand, having a high household income was found to be a protective factor for SRIM in four out of five studies (Gokceoglu & Kucukoglu, 2017; Herrera, 2008; Li et al, 2008; Sahin et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The SRIM risk factors very consistently identified were low maternal education (five of six studies examining this risk factor) (Gokceoglu & Kucukoglu, 2017; Menekseet al, 2021; Robert et al, 2014; Rodrigo et al, 2019; Segura‐Millán et al, 1994), primiparity (five of nine studies) (Brownell et al, 2012; Hillervik‐Lindquist, 1992; Keemer, 2013; Kent et al, 2021; Kirkland & Fein, 2003), maternal employment (three of three studies) (Chuang et al, 2007; Sahin et al, 2013; Sun‐Hee, 2019), and younger maternal age (five of six studies) (Amine et al, 1989; Brown et al, 2014; Gokceoglu & Kucukoglu, 2017; López et al, 2013; Rodrigo et al, 2019). On the other hand, having a high household income was found to be a protective factor for SRIM in four out of five studies (Gokceoglu & Kucukoglu, 2017; Herrera, 2008; Li et al, 2008; Sahin et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, mothers should be confident that they can produce enough milk to meet the needs of their babies even in the first few days after delivery (McGuire, 2018 ). In order to reinforce mothers' breastfeeding self‐efficacy, it is necessary to provide mothers and their family members with breastfeeding knowledge in the prenatal period, including breastfeeding techniques, breastfeeding benefits, normal patterns of infant breastfeeding behaviour, physiology of breast milk production, resolution of breastfeeding problems, etc., (Demirci et al, 2020 ; Lauwers & Swisher, 2010 ; Rodrigo et al, 2018 ; Safon et al, 2017 ). If a mother is concerned that her baby is not getting sufficient breast milk, health professionals can use more reliable parameters to evaluate her baby, such as the number of wet diapers and stools (American Academy of Pediatrics, 2005 ), infant alertness, skin colour, muscle tone, and consistent weight gain and growth (Amir, 2006 ; Neifert, 2004 ; Shrago et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, perceived insufficient milk supply (PIMS) is one of the main reasons given for formula supplementation and breastfeeding discontinuation (Gatti, 2008 ; Peacock‐Chambers et al, 2017 ; Rodrigo et al, 2018 ). PIMS is the mother's belief that the quality or quantity of her breast milk is insufficient to meet the infant's hunger or nutritional needs (Hill & Aldag, 1993 ; McCarter‐Spaulding & Kearney, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on postnatal distress and breast milk production suggested that the postnatal mood may be indirectly related to milk secretion by influencing oxytocin release [82,83]. Postnatal depression was associated with reduced length of exclusively breastfeeding period [84] and women with postnatal distress had higher risks of PIM [18,84]. However, no difference of breast milk volume was observed between women with and without perinatal depression [84].…”
Section: Hypotheses Of the Mechanism Of Saccharomyces Cerevisiae Yeast-based Supplement On Breast Milk Productionmentioning
confidence: 99%
“…Women's perception of milk supply may be influenced by health professionals, family, and friends. If these people questioned the mother's milk supply, the mother would perceive her milk supply as inadequate [18].…”
Section: Introductionmentioning
confidence: 99%